2011
DOI: 10.1542/peds.2010-3460
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tc-99m DMSA Scan for Identifying Dilating Vesicoureteral Reflux in Children: A Meta-analysis

Abstract: Controversy exists regarding the type and/or sequence of imaging studies needed during the first febrile urinary tract infection (UTI) in young children. Several investigators have claimed that because acute-phase Tc-99m dimercaptosuccinic acid (DMSA) renal-scan results are abnormal in the presence of dilating vesicoureteral reflux, a normal DMSA-scan result makes voiding cystourethrography (VCUG) unnecessary in the primary examination of infants with UTI. To evaluate the accuracy of acute-phase DMSA scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
2
27
0
5
Order By: Relevance
“…The meta-analysis study shows the pooled sensitivity and specificity of DMSA scan were only 79% and 53%, respectively, for the patient-based analysis [26]. Data are quite similar to those in our study, with sensitivity 82.1% and specificity 56.1%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The meta-analysis study shows the pooled sensitivity and specificity of DMSA scan were only 79% and 53%, respectively, for the patient-based analysis [26]. Data are quite similar to those in our study, with sensitivity 82.1% and specificity 56.1%.…”
Section: Discussionsupporting
confidence: 87%
“…The limitations of our study are that the quality of performance of prenatal US is not assured, and the information of voiding dysfunction is not evaluated. The use of DMSA scan is criticized for higher costs, longer duration, radiation exposure, and requirement of special equipment [26]. As pointed out by Flynn, it is difficult, even in developed countries, to schedule a every young child with febrile UTI for both US and DMSA scan during the acute episode [32].…”
Section: Discussionmentioning
confidence: 99%
“…30 There are several reasons for this discrepancy. Compared with patients from the studies included in the metaanalysis, our study sample is highly heterogeneous and it may have included children with recurrent UTIs as well.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] However, conclusions from two meta-analyses have demonstrated that acute-phase DMSA scintigraphy for predicting VUR was not accurate enough in children with fUTI. [18,19] In addition, it should be emphasized that there is no certain distinction between radiologically revealed congenital renal dysplasia and parenchymal inflammatory changes associated with acute pyelonephritis in young children. Therefore, the defects resulting from congenital dysplasia may be mistakenly identified as acute pyelonephritis on initial DMSA imaging.…”
Section: Discussionmentioning
confidence: 99%